IMPELEMENTASI AFTA : TANTANGAN DAN PENGARUHNYA TERHADAP INDONESIA - Ratna Shofi Inayati (Pusat Penelitian Politik, 2010)
Regional economic integration under AFTA can provide an important building blockfor the establishment of an ASEAN Economic Community AEC The establishment ofan AEC requires afreeflow ofgoods and services among member countries A successful AFTA is vitalfor maintaining regionalpeace and security which is essential for long term ASEAN economic progress Significant progress has been made already in the implementation of their tariff reduction commitment under AFTA However the second phase of economic integration remove or harmonization ofNon TariffBarrier s NTB poses a more challenging and difficult task due mainly to the significant differences that exist among each countries in terms of economic development national priorities and levels of efficiency